Geotechnology as support for the management of conservation units in Brazil's Pantanal - Miranda, Ciomara de Souza; Cândido, Anny Keli Aparecida Alves; Mioto, Camila Leonardo; da Silva, Normandes Matos; Paranhos Filho, Antônio Conceição; Pott, Arnildo (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2017)
The aim of this paper is to study temporal variations in vegetation indices as a tool for monitoring the integral protection conservation units (parks, reserves, and ecological stations) in the Brazilian Pantanal, giving support to environmental management actions in these areas. The study was carried out in five conservation units. Evaluated data, beside the Normalized Difference Vegetation Index (NDVI), included information on wildfires and deforestation. Analyses showed that the Taiamã Ecological Station, the Pantanal Matogrossense National Park, and the Encontro das Águas State Park presented high vegetation indices, showing their effectiveness as areas of environmental protection. Although this latter state park presented one fire hotspot in 2015, there was significant improvement in this park. The Guirá State Park and the Pantanal of Rio Negro State Park presented relatively low NDVI values when compared with other analysed areas. The aggravating factor was that in the Rio Negro park 36 fire hotspots occurred in 2007, demonstrating the need for more vigorous monitoring and management of this protected area.
Keywords: Landsat; NDVI; Remote sensing; Surface reflectance